Comparison of the content of taste and nutrition-related non-volatile compounds in cultivated and wild blueberry varieties in Northeast China - Xu Xie; Jinlong Tian; Yuehua Wang; Chi Shu; Hailong Gui; Zhen Cheng; Zeming Wang; Ziqi Song; Qilin Tian; Bosu Wen; Bin Li (Food Chemistry: X)
This study compared the taste and nutrition related metabolites of wild blueberry (WB) and cultivated blueberry (CB) varieties in Northeast China based on widely targeted metabolomics. A total of 858 metabolites were identified, of which 254 showed significant differences. 16 carbohydrates were significantly higher in CBs than in WB, while 11 organic acids were the opposite. Otherwise, 24 flavonoids have significant advantages in WB, while amino acids and their derivatives have specific advantages in WB and CBs, which may determine the differences in fruit aroma and taste between the two. In addition, we found that “alanine, aspartate, and glutamate metabolism” is the most critical differential metabolic pathway among WB and CBs; fumaric acid, succinic acid, L-glutamic acid, and L-argininosuccinate are considered key biomarkers for distinguishing WB from CBs. This study will provide a reference for Chinese blueberries' scientific introduction of seeds, comprehensive development and effective differentiation of related products.